(Alkyl-ω-ol)triphenyltin(IV)-Loaded Mesoporous Silica as Biocompatible Potential Neuroprotectors: Evaluation of Inhibitory Activity Against Enzymes Associated with the Pathophysiology of Alzheimer’s Disease - Kristina Milisavljević; Žiko Milanović; Jovana Matić; Marko Antonijević; Vladimir Simić; Miljan Milošević; Marijana Kosanić; Goran N. Kaluđerović (Nanomaterials)
Alzheimer’s disease (AD) is a progressive neurodegenerative disorder characterized by synaptic dysfunction and neuronal loss due to the accumulation of amyloid-β peptides and tau proteins. In the pursuit of novel neuroprotective strategies, organotin(IV) compounds have garnered attention due to their unique chemical and biological properties. This study evaluates the inhibitory potential of two triphenyltin(IV) derivatives—(3-propan-1-ol)triphenyltin(IV) (Ph3SnL1) and (4-butan-1-ol)triphenyltin(IV) (Ph3SnL2)—in both free form and immobilized into mesoporous silica SBA-15~Cl, targeting acetylcholinesterase (AChE), a key enzyme involved in AD pathophysiology. The SBA-15~Cl|Ph3SnL2 nanostructures exhibited the most potent inhibitory activity against AChE (IC50 = 0.58 μM), significantly outperforming the standard drug galantamine. Molecular docking, molecular dynamics simulations, and MM/GBSA and MM/PBSA analyses confirmed the stability and selectivity of interactions with AChE, primarily driven by hydrophobic interactions. Compound transport was also simulated using a multi-scale 3D mouse brain model to evaluate brain tissue distribution and blood–brain barrier permeability. The results highlight the strong potential of SBA-15-loaded organotin(IV) compounds as biocompatible neuroprotective agents for novel treatments of neurodegenerative diseases.